Anemia dalam Kehamilan Trimester III dan Kejadian Perdarahan Postpartum Primer - Fitri Ikhtiarinawati Fajrin; Husnul Muthoharoh; Martha Marwahzuma (FORIKES, 2022)
The World Health Organization (WHO) says that the main cause of maternal death is bleeding. More than two thirds of deaths are due to primary postpartum hemorrhage. Anemia is known as a cause of primary postpartum hemorrhage due to a lack of hemoglobin in the blood which can cause a lack of oxygen to the cells of the body and brain, including the uterus. This study aims to analyze the relationship between the incidence of anemia and the incidence of postpartum hemorrhage, with a cross-sectional design. Data collection in this study was carried out for 3 months, from October to December 2021 in the VK Room, Maduran Health Center, Lamongan Regency. The collected data were analyzed using the Chi-square test. The results of data analysis showed a value of p = 0.015. It was concluded that there is a relationship between the incidence of anemia in pregnancy and the incidence of primary postpartum hemorrhage.Keywords: anemia; pregnancy; primary postpartum hemorrhage ABSTRAK World Health Organization (WHO) mengatakan bahwa penyebab utama kematian ibu adalah perdarahan. Lebih dari dua pertiga kematian adalah karena perdarahan postpartum primer. Anemia dikenal sebagai penyebab perdarahan postpartum primer karena kekurangan hemoglobin dalam darah yang dapat menyebabkan kekurangan oksigen ke sel-sel tubuh dan otak, termasuk rahim. Penelitian ini bertujuan untuk menganalisis hubungan antara kejadian anemia dengan kejadian perdarahan postpartum, dengan rancangan cross-sectional. Pengambilan data pada penelitian ini dilaksanakan selama 3 bulan yaitu pada bulan Oktober sampai Desember 2021 di Ruang VK, Puskesmas Maduran, Kabupaten Lamongan. Data yang telah terkumpul dianalisis menggunakan uji Chi-square. Hasil analisis data menunjukkan nilai p = 0,015. Disimpulkan bahwa ada hubungan antara kejadian anemia dalam kehamilan dengan kejadian perdarahan postpartum primer.Kata kunci: anemia; kehamilan; perdarahan postpartum primer